2012
DOI: 10.1016/j.ijgo.2011.11.015
|View full text |Cite
|
Sign up to set email alerts
|

The role of genital pathogens in morbidity following diathermy loop excision of the transformation zone of the uterine cervix

Abstract: Genital pathogens are very common among patients with CIN and do not affect the occurrence or severity of pain, discharge, or postoperative bleeding after diathermy LETZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…An explanation of the relatively common ASC found in the genital epithelium of pups could be shifts in the local microbiome during neonatal development, as has been reported for humans [61] and mice [62], or alternatively, infections by other pathogens, such as Candida, Chlamydia, Trichomonas and Mycoplasma [41][42][43], some of which are common inhabitants of the genital tracts of otariid pinnipeds [13,63]. These possibilities need to be explored in the future.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…An explanation of the relatively common ASC found in the genital epithelium of pups could be shifts in the local microbiome during neonatal development, as has been reported for humans [61] and mice [62], or alternatively, infections by other pathogens, such as Candida, Chlamydia, Trichomonas and Mycoplasma [41][42][43], some of which are common inhabitants of the genital tracts of otariid pinnipeds [13,63]. These possibilities need to be explored in the future.…”
Section: Discussionmentioning
confidence: 95%
“…LSIL includes mild dysplasia and cervical intraepithelial neoplasia grade I [40]. ASC refers to the presence of atypical cells that do not tend to transform to a malignant state and could be caused by infection by various pathogens, such as Trichomonas vaginalis, Mycoplasma genitalium, Chlamydia trachomatis, Candida and Streptococcus agalactiae [41][42][43].…”
Section: Cytologymentioning
confidence: 99%
“…In addition to serving as a physical barrier, CMPs contain a variety of antimicrobial compounds including cytokines, lactoferrin, lysozyme, and AMPs (Hein et al, 2002;Lee et al, 2011;Arko et al, 2012). Thus, the CMP may be intrinsically antimicrobial and serve as a checkpoint in preventing vaginal pathogens from ascending through the cervix to invade the uterus (Hein et al, 2001;Becher et al, 2009).…”
Section: The Cervical Mucus Plug: a Barrier To Ascensionmentioning
confidence: 99%
“…During pregnancy, a dense and viscous mucoid structure known as the cervical mucus plug (CMP) forms in the cervical canal. In addition to acting as a physical barrier, CMPs can harbor pro-inflammatory cytokines as well as a variety of antimicrobial compounds, including lysozyme, lactoferrin, calprotectin, and secretory leukoprotease inhibitor 1, which vary by individual [171][172][173]. Although our understanding of the CM P's role in defending against pathogenic bacteria is poor, a recent study examining 60 human CMPs showed that CMP-associated proteins activated leukocytes in whole blood, resulting in increased GBS killing [174].…”
Section: Cmp Compositionmentioning
confidence: 99%
“…Maternal CPS-specific antibody production Associated with asymptomatic vaginal colonization [149,150] Associated with enhanced vaginal clearance [150] Associated with reduced risk of early onset disease in newborns [151] CPS-based conjugate vaccines [152][153][154][155][156][157][158] Mucosal immunity Neutrophils [97,98,161], macrophages [97], mast cells [99] promote clearance of GBS from the vagina Soluble inflammatory mediators promote clearance of GBS from the vagina [97,98,161] IL-17 and IL-17+ cells promoted clearance of persistent strain [161] Humoral immunity in vaginal mucosa promotes clearance of GBS from the vagina [162] Deficiencies may increase risk for invasive disease Mucosal vaccination tested using in vivo mouse models [162] Vaginal epithelial exfoliation Disrupts barrier function of vaginal epithelia, promotes ascending GBS infection [170] None known Cervical mucus plug Physical barrier between lower genital tract and uterus Can secrete pro-inflammatory cytokines, chemokines (not tested in vivo) [171][172][173] Can retain antibiotic drugs that kill GBS [174] Antimicrobial compounds within CMPs insufficient to kill GBS [174] None known Mast cell chymase Inhibits GBS's ability to bind fibronectin [87] None known…”
Section: Factor Effect On Gbs Colonization/virulence Interventionmentioning
confidence: 99%